ANALISIS PENGARUH COUNTRY OF ORIGIN (COO) DAN BRAND IMAGE TERHADAP PERCEIVED QUALITY DAN PURCHASE INTENTION SMARTPHONE OPPO DI KOTA PEKANBARU - Simanjuntak, Bernando; Restuti, Sri; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze the influence of Country of Origin and Brand Image on Perceived Quality and Purchase Intention OPPO Smartphone in Pekanbaru. The sampling method using a census of all the population being sampled. The data used in this study is primary data obtained from questionnaires. The total sample of 96 respondents who are employees of Hotel Comfort Dumai. The analysis technique used is path analysis method. The results showed that variable Country of Origin and Brand Image has positive and significant effect on Perceived Quality and Purchase Intention. The variable that has the most dominant influence on Purchase Intention is a Brand Image variable. From this study obtained Rsquare value of 0,803 for the influence on Purchase Intention, this means that 80.3% Purchase Intention variable can be explained by Country of Origin, Brand Image and Perceived Quality variable and the remaining 19.7% is explained by other variables outside the equation.Keywords: Country of Origin, Brand Image, Perceived Quality, Purchase Intention